PRELEMINARY ANALYTICAL STUDY OF PANCHTIKTA GHRITA - Pankaj Rai; Laxmi Narayan Gupta; Siddaram Arawatti; Seema Krishna Murthy (International Journal of Applied Ayurved Research, 2015)
Panchtikta Ghrita was processed as per the process of Snehapaka procedure described Ayurvedic formulary of India.It contained Panchtikta that is Nimba (Azadirachta indica ,Patola (Luffa acutangula ), Vyaghri ,Guduchi ,Vasa ( Adhatoda vasica ).They are used in the form of decoction in the preparation of Panchtikta Ghrita. Paste of Triphala – Haritaki (Terminalia chebula), Vibhitaki (Terminalia bellirica) Amla (Emblica officinalis) is also prepared and used in Panchtikta ghrita. Mixture were mixed in Purana Ghrita and heated for three hours at 100°C every day for two days. On the second day Ghrita was filtered to obtain the finished product. In this manner, three samples of Panchtikta Ghrita were prepared. To understand the changes that occurred during the preparation, Panchtikta Ghrita and Purana Ghrita were analyzed by using modern parameters such as Acid value, Saponification value, iodine value, peroxide value and so on.